Acupotomy for Occipital Neuralgia: A Narrative Review - Han Eung Jo; Yae Gi Min; Hyang Gi Lim; Jung Hee Lee; Hyun-Jong Lee; Sung Chul Lim; Yun Kyu Lee; Jae Soo Kim (Journal of Acupuncture Research)
This analysis of clinical research trends aims to assess the effectiveness and safety of autotomy for occipital neuralgia by reviewing randomized controlled trials (RCTs) on autotomy for occipital neuralgia that were published between October 2008 and January 2021. A two-step study selection process was conducted by searching both domestic and international databases. Of the initial 305 studies, 11 RCTs were selected for in-depth analysis. The studies were reviewed based on publication year and country, number of participants, illness duration, treatment method, type of treatment tool, stimulation site, stimulation method and depth, treatment frequency, evaluation tool, treatment outcome, adverse events, follow-up data, and potential bias. The analysis of the selected RCTs revealed that autotomy appeared to be effective in reducing the symptoms of occipital neuralgia, with a low incidence of adverse events, suggesting a favorable safety profile. The findings suggest that autotomy is a potentially effective and safe treatment for occipital neuralgia. However, further research is needed to confirm these findings.